Bribri, a new small red bean variety for Costa Rica. - Hernández, Juan Carlos (2006)
The line MD 23-24 was introduced and tested in Costa Rica between 1996 and 1999, which served as the precursor of the Bribri bean variety. It was bred, at the Escuela Agrícola Panamericana Zamorano, by crossing (RAB 310/XAN 155) X (DOR 391/POMPADOUR G). The variety characterizes by showing a small bright red grain, with a II-B Type growth habit, an erect bearing and a vegetative cycle from 76-80 days. The two main life zones where it was evaluated were the bh-T (tropical humid forest) and the bmh-P (very humid pre-mountainous forest). Small commercial farms with low fertility soils prevailed in most of the evaluated localities. The Bribri variety outstood in average yield by 17.2% the national control and by 13,4% the local control. Its yield was 8.5% higher than the average yield of all the assays. The verifying and the validation stages were conducted based on the technology applied by the farmers in nine out of eleven localities. Bribri out-yielded the local controls in 67% of the plots at the verifying phase (with an average of 15.5% more kg/ha) and in 80% of the validation plots (with an average of 7.5% more kg/ha). Besides, it showed tolerance to web-blight (Thanatephorus cucumeris (A.B. Frank) Donk).